2018
DOI: 10.1016/j.cobme.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Testing thousands of nanoparticles in vivo using DNA barcodes

Abstract: Nanoparticles improve drug efficacy by delivering drugs to sites of disease. To effectively deliver a drug in vivo, a nanoparticle must overcome physical and physiological hurdles that are not present in cell culture, yet in vitro screens are used to predict nanoparticle delivery in vivo. An ideal nanoparticle discovery pipeline would enable scientists to study thousands of nanoparticles in vivo. Here, we discuss technologies that enable high throughput in vivo screens, focusing on DNA barcoded nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 58 publications
0
51
0
1
Order By: Relevance
“…We reasoned that measuring hundreds of distinct LNPs in vivo would provide the best chance of identifying nanoparticles that deliver mRNA to new cell types. Using DNA barcodes ( 17 , 20 22 ), we previously quantified how >350 LNPs distributed in vivo. However, biodistribution is necessary, but not sufficient, for functional RNA delivery.…”
mentioning
confidence: 99%
“…We reasoned that measuring hundreds of distinct LNPs in vivo would provide the best chance of identifying nanoparticles that deliver mRNA to new cell types. Using DNA barcodes ( 17 , 20 22 ), we previously quantified how >350 LNPs distributed in vivo. However, biodistribution is necessary, but not sufficient, for functional RNA delivery.…”
mentioning
confidence: 99%
“…More specifically, we found that a rationally designed ddPCR-based barcode system can quantify delivery with very high sensitivity. Previous DNA barcode technologies designed to track nanoparticle biodistribution could only compare relative biodistribution within the same cell type, but could not be used to compare biodistribution between different cell types 71 . We anticipate future studies further improving the design of QUANT barcodes by incorporating different patterns of chemical modification.…”
Section: Discussionmentioning
confidence: 99%
“…The different nanoformulations were pooled together and injected into a single mouse. The nucleic acid barcodes were recovered at a different time point from different tissues or cells, then Illumina deep sequencing was performed to accurately quantify the distinct barcodes and thus the biodistribution of different nanoparticles [ 188 , 190 ]. Careful dosing studies demonstrated that DNA barcode LNPs can be measured at a low dose, which confirms the feasibility of multiplexing hundreds of nanoparticles in a single experiment [ 188 ].…”
Section: Barcoding—a New Mode To Apply Sequences For Finding In VImentioning
confidence: 99%